Composite lithium supplementing material and preparation method thereof, positive electrode material and secondary battery

By using one-dimensional carbon materials to connect with multidimensional carbon materials and combining catalysts in lithium-rich materials to form a conductive network, the problems of poor conductivity and high deliquency potential of lithium-rich materials are solved, and its performance in secondary batteries is improved. Cycle life.

CN119297232APending Publication Date: 2025-01-10SHENZHEN DYNANONIC INNOVAZONE NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411380596.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing lithium-rich materials have poor conductivity and high deliquency potential, which leads to their inability to fully release lithium ions under low voltage conditions, and their kinetic performance is poor, which limits their application in secondary batteries.

Method used

Using composite lithium supplement material, by connecting one-dimensional carbon material with multi-dimensional carbon material and combining catalysts, a stronger conductive network and rich catalyst-loaded active sites are formed, which reduces the deliquency potential of lithium-rich materials and improves its conductivity.

Benefits of technology

It significantly reduces the deliquency potential of lithium-rich materials, improves its adaptability with the positive electrode active material, enhances the cycling performance and energy density of the battery, and extends the cycling life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297232A_ABST
    Figure CN119297232A_ABST
Patent Text Reader

Abstract

The invention relates to a composite lithium supplementing material and a preparation method thereof, a positive electrode material and a secondary battery, the composite lithium supplementing material comprises a lithium-rich material, a one-dimensional carbon material, a multi-dimensional carbon material and a catalyst, the chemical formula of the lithium-rich material comprises Lix1Cy1Oz1, 0 lt, 0 lt, 0 lt, 0 lt, 0 lt, 0 lt, 0 lt, 0 lt, 0 lt, 0 lt, 0 lt, 0 lt, 0 lt, 0 lt, 0 lt, 0 lt, 0 X1 < = 2, y1gt; 0, z1gt; 0; the one-dimensional carbon material is connected with the multi-dimensional carbon material, at least part of the catalyst is loaded on the one-dimensional carbon material, and the lithium-rich material is combined with the one-dimensional carbon material and / or the multi-dimensional carbon material. The composite lithium supplementing material provided by the invention can solve the problems of poor conductivity and high lithium removal potential of a lithium-rich material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a composite lithium supplement material and a preparation method thereof, a positive electrode material and a secondary battery. Background Art

[0002] During the first charge and discharge process of the battery, the electrolyte will undergo a reduction decomposition reaction on the surface of the negative electrode and form a layer of solid electrolyte interface film (SEI film). The formation of the SEI film will consume a large amount of active lithium, resulting in a decrease in the actual energy density of the battery compared to the theoretical calculated value. During the cyclic charge and discharge process of the battery, the cracking and crushing of the positive electrode active material particles, the thickening and repair of the SEI film will continuously consume active lithium, causing a continuous decline in the battery cycle performance. In order to further improve the energy density and cycle performance of the battery, adding lithium-rich materials to the positive electrode as a lithium supplement can effectively alleviate the problems of low battery energy density, low first-cycle efficiency, and poor cycle life.

[0003] However, current lithium-rich materials have problems such as poor conductivity and high delithiation potential, which make it impossible for lithium-rich materials to fully release lithium ions under low voltage conditions. In addition, the transmission path of electrons and ions in lithium-rich materials is long, and the kinetic performance is poor. Summary of the invention

[0004] The purpose of the present invention is to provide a composite lithium supplement material and a preparation method thereof, a positive electrode material and a secondary battery, so as to solve the problems of poor conductivity and high lithium desorption potential of lithium-rich materials.

[0005] To achieve the purpose of this application, this application provides the following technical solutions:

[0006] In a first aspect, the present invention provides a composite lithium supplement material, a lithium-rich material, a one-dimensional carbon material, a multi-dimensional carbon material and a catalyst, wherein the chemical formula of the lithium-rich material includes Li x1 C y1 O z1 , where 0<x1≤2,y1> 0, z1>0; the one-dimensional carbon material is connected to the multi-dimensional carbon material, at least a portion of the catalyst is loaded on the one-dimensional carbon material, and the lithium-rich material is combined with the one-dimensional carbon material and / or the multi-dimensional carbon material.

[0007] In one embodiment, the multi-dimensional carbon material is connected to the outside of the one-dimensional carbon material.

[0008] In one embodiment, the multidimensional carbon material is a porous structure having pores, and the one-dimensional carbon material extends into the pores of the multidimensional carbon material.

[0009] In one embodiment, the multi-dimensional carbon material has macropores, and the one-dimensional carbon material is interspersed in the macropores.

[0010] In one embodiment, mesopores or micropores are distributed in the multidimensional carbon material.

[0011] In one embodiment, the porosity of the three-dimensional porous carbon is 60% to 85%.

[0012] In one embodiment, the one-dimensional carbon material is doped with non-metallic elements, and the non-metallic elements include at least one of O, N, S, and P.

[0013] In one embodiment, the one-dimensional carbon material and the multi-dimensional carbon material are connected by chemical bonds, and the chemical bonds include one or more of CC, CS, CN, CO, CP, C=C, C=O, and C=N.

[0014] In one embodiment, the one-dimensional carbon material has a hollow structure, and at least a portion of the catalyst is contained in the one-dimensional carbon material.

[0015] In one embodiment, the catalyst includes a first catalyst and a second catalyst that are different, and the first catalyst and the second catalyst are interconnected to form a heterojunction.

[0016] In one embodiment, the mass ratio of the sum of the one-dimensional carbon material and the multi-dimensional carbon material to the catalyst is 10:(1-10).

[0017] In one embodiment, the specific surface area of ​​the one-dimensional carbon material is 100 m 2 / g~400m 2 / g.

[0018] In one embodiment, the specific surface area of ​​the multidimensional carbon material is 1000 m 2 / g~3000m 2 / g.

[0019] In one embodiment, the particle size of the catalyst is 2 nm to 50 nm.

[0020] In one embodiment, the one-dimensional carbon material, the multi-dimensional carbon material and the catalyst together constitute a catalytic material, and the catalytic material is embedded in the lithium-rich material.

[0021] In one embodiment, the one-dimensional carbon material, the multi-dimensional carbon material and the catalyst together constitute a catalytic material, and the catalytic material is coated on the periphery of the lithium-rich material.

[0022] In one embodiment, the mass ratio of the lithium-rich material to the catalytic material is 100:(5-35).

[0023] In a second aspect, the present invention provides a method for preparing a composite lithium-supplementing material, comprising: mixing a one-dimensional carbon material and a precursor of a catalyst with a multidimensional carbon material respectively, or mixing a precursor of the catalyst and a precursor of the one-dimensional carbon material with the multidimensional carbon material respectively, and obtaining a catalytic material after heat treatment; mixing the catalytic material and a lithium-rich material together to obtain a composite lithium-supplementing material.

[0024] In a third aspect, the present invention further provides a positive electrode material, which includes an active material and a composite lithium-replenishing material, wherein the composite lithium-replenishing material includes the composite lithium-replenishing material described in the first aspect, or the positive electrode material includes the composite lithium-replenishing material obtained by the preparation method of the composite lithium-replenishing material described in the second aspect.

[0025] In a fourth aspect, the present invention further provides a secondary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the positive electrode material described in the third aspect.

[0026] The composite lithium-supplementing material provided by the present invention comprises a one-dimensional carbon material, a multi-dimensional carbon material and a catalyst, wherein the one-dimensional carbon material and the multi-dimensional carbon material are connected to form a stronger conductive network, thereby improving the conductivity of the lithium-rich material; and the one-dimensional carbon material and the multi-dimensional carbon material can also provide abundant active sites for catalyst loading, thereby improving the catalytic efficiency of the catalyst; in this way, the present invention can catalyze the lithium-rich material through the catalyst to achieve the purpose of reducing its delithiation potential, and achieve the purpose of improving the conductivity of the lithium-rich material through the one-dimensional carbon material and the multi-dimensional carbon material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0028] Figure 1 is a schematic structural diagram of a composite lithium supplement material according to an embodiment;

[0029] Figure 2 is a schematic structural diagram of a catalytic material according to an embodiment;

[0030] Figure 3 is a flow chart for preparing a composite lithium supplement material according to an embodiment;

[0031] Figure 4 yes Figure 3 Flowchart of step A10 in FIG.

[0032] Figure 5is a schematic structural diagram of a catalytic material according to another embodiment;

[0033] Figure 6 yes Figure 5 The enlarged schematic diagram of point A in the middle;

[0034] Figure 7 is a schematic structural diagram of a composite lithium supplement material according to another embodiment;

[0035] Figure 8 is a flow chart for preparing a composite lithium supplement material according to another embodiment;

[0036] Fig. 9 yes Figure 8 Flowchart of step B10 in FIG. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0038] It should be noted that when a component is said to be "fixed to" another component, it can be directly on the other component or there can be a central component. When a component is said to be "connected to" another component, it can be directly connected to the other component or there can be a central component at the same time.

[0039] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this application and in the specification are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items.

[0040] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0041] In the first aspect, the present invention provides a composite lithium supplement material, please refer to Figure 1 and Figure 2 The composite lithium supplement material includes a lithium-rich material 100, a one-dimensional carbon material 10, a multi-dimensional carbon material 20 and a catalyst 30, wherein the chemical formula of the lithium-rich material 100 includes Li x1 C y1 O z1, where 0<x1≤2,y1> 0, z1>0; the one-dimensional carbon material 10 is connected to the multidimensional carbon material 20, at least part of the catalyst 30 is loaded on the one-dimensional carbon material 10, and the lithium-rich material 100 is combined with the one-dimensional carbon material 10 and / or the multidimensional carbon material 20. Optionally, the one-dimensional carbon material 10, the multidimensional carbon material 20 and the catalyst 30 together constitute the catalytic material 200.

[0042] The lithium-rich material 100 is the main body for replenishing lithium, which can contribute a large amount of lithium ions. During the first charging process, the lithium (Li) in the lithium-rich material 100 can be released and migrated to the negative electrode of the battery to offset the irreversible lithium loss caused by the formation of the SEI film, thereby increasing the total capacity and energy density of the battery.

[0043] However, most of the existing high-capacity lithium-rich materials 100 have problems with poor conductivity and high detachment potential, which makes such lithium-rich materials 100 unable to match most commercial positive electrode active materials, which greatly hinders the commercial application of lithium-rich materials 100. In addition, the higher voltage also causes the lithium-rich material 100 to produce gas during the first charge and discharge of the lithium-ion battery. The generated gas cannot be discharged in time, resulting in reduced safety and performance of the lithium-ion battery. Therefore, how to solve the poor conductivity and high detachment potential of the lithium-rich material 100 has become the key.

[0044] Therefore, the present invention combines the catalytic material 200 with the lithium-rich material 100, or combines the lithium-rich material 100 with the catalytic material 200, and uses the catalytic material 200 to catalyze the lithium-rich material 100 to reduce the delithiation potential of the lithium-rich material 100, thereby improving the compatibility of the lithium-rich material 100 and the positive electrode active material.

[0045] In one embodiment, the lithium-rich material Li x1 C y1 O z1 Including but not limited to one or more of Li2C2O4 (lithium oxalate), Li2CO3 (lithium carbonate), Li2C3O3 (lithium trioxide), Li2C4O4 (lithium butynedioate), Li2C6O6, Li2C3O5 (lithium acetonate), and Li2C4O6. It can be understood that the lithium-rich material Li x1 C y1 O z1 Has a high theoretical capacity (>525mAhg -1 ) and good air stability, it is considered to be an attractive cathode pre-lithiation additive. However, it has a high delithiation potential (>4.7V), which cannot match most commercial cathode materials, and its poor conductivity greatly hinders its commercial application.

[0046] In one embodiment, the lithium-rich material 100 may further include other lithium-supplementing agents with a relatively high decomposition voltage, mainly including lithium-supplementing agents with a de-lithiation potential above 4V, such as Li2O (de-lithiation potential 4.5V), Li2O2 (de-lithiation potential 4.3V), LiOH (de-lithiation potential 4.8V), Li4SiO4 (de-lithiation potential 4.5V), Li3PO4 (de-lithiation potential exceeding 4V), Li2CO3 (de-lithiation potential 4.7V), and Li5FeO4 (de-lithiation potential 4V). These lithium-rich materials 100 also have relatively high capacities. However, de-lithiation of these lithium-rich materials 100 requires a relatively high charging voltage, presenting the technical problem of a high de-lithiation potential. At the same time, the relatively high voltage also causes oxygen to be generated during the first charge and discharge of the lithium-rich material 100 in a lithium-ion battery. The generated oxygen further oxidizes, leading to the oxidation and decomposition of the electrolyte, thereby reducing the safety and performance of the lithium-ion battery. These lithium-rich materials 100 with a relatively high decomposition voltage are also difficult to be compounded with conventional cathode materials (such as the de-lithiation potential of lithium iron phosphate is about 3.5V), which limits the wide application of the composite lithium-supplementing material.

[0047] Optionally, the lithium-rich material 100 may further include a binary lithium-supplementing agent and / or a ternary lithium-supplementing agent. The general chemical formula of the lithium-rich material 100 corresponding to the binary lithium-supplementing agent is Li x2 K y2 , where K is at least one element among S, P, N, F, B, Se, and Te, 1 ≤ x2 ≤ 5, 0 < y2. The binary lithium-supplementing agent includes but is not limited to at least one of Li3N, Li2S, LiF, Li3P, and Li2Se.

[0048] Optionally, the chemical formula of the lithium-rich material 100 corresponding to the ternary lithium-supplementing agent is Li x3 M y3 O z3 , where M is at least one element among Fe, Ni, Mn, Cu, Zn, Co, Cr, Zr, Sb, Ti, V, Mo, Sn, etc., 1 ≤ x3 ≤ 8, 0 < y3, 0 < z3 < 7. In a specific embodiment, the lithium-rich material 100 may be at least one of Li5FeO4, Li6MnO4, Li6CoO4, Li6ZnO4, Li2NiO2, Li2CuO2, Li2CoO2, Li2MnO2, Li2Ni 0.5 Mn 1.5 O4, Li2Ni d Cu (1-d) O2 (0 < d < 1), etc.

[0049] Optionally, the chemical formula of the lithium-rich material 100 may also be Li 1+x4 A y4 O z4, where 0 <x4≤1.2,1≤y4<3,z4> 0, A includes at least one of Ni, Fe, Mn, Co, Cr, V, Mo, Ti, Nb, Zr, Cu, and Mg. The lithium-rich materials 100 can be used as lithium supplements or directly as positive electrode materials. Exemplarily, the lithium-rich material 100 includes at least one of Li2CuO2, Li2NiO2, and Li2MnO2.

[0050] The lithium-rich material 100 mentioned above may be undoped or modified by doping, or may be surface coated, pre-lithiation treated, etc. These lithium-rich materials 100 have high theoretical capacity and structural stability, can provide sufficient lithium ions, effectively replenish the irreversible lithium ions consumed by the formation of SEI film at the negative electrode, and improve the initial efficiency and overall electrochemical performance of the battery. It should be noted that the above lithium-rich materials 100 have long been industrially produced and do not require independent synthesis, so the raw material cost is low and the purity is high; and the selected lithium-rich materials 100 have a high theoretical capacity, and the synthesized composite lithium-supplementing material has a high specific charging capacity and an excellent lithium-supplementing effect.

[0051] The one-dimensional carbon material 10 includes, but is not limited to, one or more of carbon nanotubes (CNTs), carbon nanorods, and carbon nanofibers; in a specific embodiment, the one-dimensional carbon material 10 is preferably a carbon nanotube. In addition, the one-dimensional carbon material 10 is doped with non-metallic elements, and the non-metallic elements include at least one of O, N, S, and P. Optionally, the non-metallic elements doped on the one-dimensional carbon material 10 are nitrogen and sulfur, and the nitrogen and sulfur are doped on the active sites of the one-dimensional carbon material 10.

[0052] In this aspect, the multidimensional carbon material 20 is preferably a two-dimensional carbon material. In a specific embodiment, the multidimensional carbon material 20 is preferably a graphene nanosheet (GNS). It should be explained that although the one-dimensional carbon material 10 and the two-dimensional carbon material both belong to the general category of carbon materials, the physical and chemical properties exhibited by the one-dimensional carbon material 10 and the two-dimensional carbon material are different due to their different structures. The present invention compounds the one-dimensional carbon material 10 and the two-dimensional carbon material in order to make full use of the lithium performance advantages provided by the two to obtain a composite material performance of 1+1>2.

[0053] Taking carbon nanotubes and graphene nanosheets as examples, carbon nanotubes are a type of one-dimensional quantum material with a special structure, which is a single layer or multiple layers of graphite sheets curled at a certain angle into a hollow seamless tubular structure. Graphene nanosheets are two-dimensional materials composed of a single layer of carbon atoms arranged in a hexagonal grid, with a single atomic layer thickness, and can also be stacked into a multi-layer structure to form graphene microsheets. Carbon nanotubes show advantages in mechanical properties, thermal conductivity and one-dimensional morphology, while graphene nanosheets show unique excellent properties in electrical conductivity, optical properties and two-dimensional morphology.

[0054] In this aspect, the catalyst 30 has a catalytic effect, and is mainly used to catalytically reduce the delithiation potential of the lithium-rich material 100. The activation energy of the delithiation reaction of the lithium-rich material 100 is reduced by adding the catalyst 30 to the composite lithium-supplementing material, thereby improving the reaction activity of the lithium-rich material 100. The addition of the catalyst 30 can reduce the delithiation potential of the lithium-rich material 100 to varying degrees, so that it can match the existing commercial positive electrode active materials. Specifically, in this aspect, the catalyst 30 can be loaded on the one-dimensional carbon material 10 and the two-dimensional carbon material, and preferably, the catalyst 30 is connected to the outer surface of the one-dimensional carbon material 10 and the two-dimensional carbon material.

[0055] The catalyst 30 includes a metal oxide. The general chemical formula of the metal oxide includes D1 a O b , wherein D1 is a transition metal element, D1 includes at least one of Co, Mo, W, V, Ti, Fe, Ni, Mn, Cr, Cu, and Zn, 1≤a≤3, 1≤b≤3. In a specific embodiment, the catalyst 30 includes one or more of CoO, MnO, and NiO.

[0056] The composite lithium-supplementing material provided by the present invention includes a one-dimensional carbon material 10, a multidimensional carbon material 20 and a catalyst 30, wherein the one-dimensional carbon material 10 and the multidimensional carbon material 20 are connected to form a stronger conductive network, thereby improving the conductivity of the lithium-rich material 100; and the one-dimensional carbon material 10 and the multidimensional carbon material 20 can also provide abundant active sites loaded by the catalyst 30, thereby improving the catalytic efficiency of the catalyst 30; in this way, the present invention can catalyze the lithium-rich material 100 through the catalyst 30 to achieve the purpose of reducing its delithiation potential, and achieve the purpose of improving the conductivity of the lithium-rich material 100 through the one-dimensional carbon material 10 and the multidimensional carbon material 20.

[0057] In one embodiment, the two-dimensional carbon material is connected to the outer surface of the one-dimensional carbon material 10, and multiple pieces of the two-dimensional carbon material are connected to the outer surface of the one-dimensional carbon material 10. Specifically, in this aspect, the length of the one-dimensional carbon material 10 can be greater than the width or length of the two-dimensional carbon material, so the outer surface of the one-dimensional carbon material 10 provides a larger area, so that multiple pieces of the two-dimensional carbon material can be connected.

[0058] In a specific embodiment, along the radial direction of the one-dimensional carbon material 10, two opposite sides of the one-dimensional carbon material 10 are connected to a plurality of two-dimensional carbon materials. Figure 2As shown, the one-dimensional carbon material 10 may include a first side surface and a second side surface facing each other, and along the radial direction of the one-dimensional carbon material 10, a plurality of two-dimensional carbon materials are connected to the first side surface of the one-dimensional carbon material 10, and a plurality of two-dimensional carbon materials are connected to the second side surface of the one-dimensional carbon material 10. The advantage of forming this structure of two-dimensional carbon materials on the one-dimensional carbon material 10 is that the two-dimensional carbon materials can be arranged as much as possible, and the two-dimensional carbon materials can be evenly dispersed, which can not only provide a larger specific surface area, but also avoid the material agglomeration phenomenon caused by the stacking of two-dimensional carbon materials, thereby improving the conductivity of the carbon material.

[0059] Optionally, in a specific embodiment, along the radial direction of the one-dimensional carbon material 10, the two-dimensional carbon materials are arranged alternately in sequence. Figure 2 As shown, on the first side ( Figure 2 A plurality of spaced two-dimensional carbon materials are connected on the left side of the one-dimensional carbon material 10, and on the second side ( Figure 2 The two-dimensional carbon material (on the right side of the one-dimensional carbon material 10) is arranged between two adjacent two-dimensional carbon materials on the first side. The advantage of forming this structure of the two-dimensional carbon material on the one-dimensional carbon material 10 is that the two-dimensional carbon material and the one-dimensional carbon material 10 form a conductive network (the two-dimensional carbon materials are arranged alternately), thereby improving the comprehensive conductivity of the two-dimensional carbon material and the one-dimensional carbon material 10.

[0060] In one embodiment, there are multiple one-dimensional carbon materials 10, which are interwoven to form a network structure. The two-dimensional carbon material is located in the pores (holes or gaps) between two adjacent one-dimensional carbon materials 10, and the two-dimensional carbon material connects the two adjacent one-dimensional carbon materials 10.

[0061] It can be understood that the two-dimensional carbon material connected to the outer surface of the one-dimensional carbon material 10 further provides a large specific surface area and active sites, which not only increases the loading amount of the catalyst 30, but also limits the growth of the catalyst 30, can reduce the particle size of the catalyst 30, and increase the contact area between the catalyst 30 and the carbon material and the lithium-rich material 100, thereby enhancing the catalytic effect of the catalyst 30; moreover, the two-dimensional carbon material can also cooperate with the one-dimensional carbon material 10 to form a conductive network structure. The pore space formed by the one-dimensional carbon material 10 and the two-dimensional carbon material can limit the gas generated after the lithium-rich material 100 is discharged, and prevent the gas generated by the lithium-rich material 100 from escaping the composite lithium-supplementing material, thereby reducing the impact of gas production on the battery, and ultimately achieving the purpose of improving battery performance.

[0062] In one embodiment, the one-dimensional carbon material 10 and the multidimensional carbon material 20 (two-dimensional carbon material) are connected by chemical bonds, and the chemical bonds include one or more of CC, CS, CN, CO, CP, C=C, C=O, and C=N. It can be understood that the one-dimensional carbon material 10 is doped with non-metallic elements (as described above), so the non-metallic elements in the one-dimensional carbon material 10 can form chemical bonds (such as CS) with the carbon elements in the two-dimensional carbon material; or the carbon elements in the one-dimensional carbon material 10 can also form chemical bonds (such as CC) with the carbon elements in the two-dimensional carbon material.

[0063] In the present invention, the one-dimensional carbon material 10 and the two-dimensional carbon material are not simply physically mixed and connected together. Different from the method of simply mixing two carbon materials in the prior art, the present invention mainly forms a chemical bond between the non-metallic element doped on the one-dimensional carbon material 10 and the carbon element in the two-dimensional carbon material, so as to organically combine the two together. It should be noted that the non-metallic element doped on the one-dimensional carbon material 10 (such as sulfur element) can form a CS bond with the carbon element in the two-dimensional carbon material, thereby forming a strong chemical bond of CSC between the one-dimensional carbon material 10 and the two-dimensional carbon material. In this way, not only the connection strength between the two can be improved, but also the electron conduction efficiency between the two can be improved.

[0064] Therefore, the composite lithium supplement material provided by the present invention also has the following advantages: 1) The non-metallic elements doped on the one-dimensional carbon material 10 can improve the conductivity of the one-dimensional carbon material 10, and also provide more active sites for the combination of the two-dimensional carbon material and the loading of the catalyst 30; 2) The two-dimensional carbon material is connected to the one-dimensional carbon material 10 through chemical bonds formed by non-metallic elements, which can not only promote the formation of a more complete conductive path between the carbon materials, but also the two-dimensional carbon material can provide additional specific surface area, providing more active sites for the loading of the catalyst 30, and further increasing the catalytic effect and conductive effect of the catalytic material 200; 3) The two-dimensional carbon material is connected to the one-dimensional carbon material 10 through non-metallic elements, which also enhances the connection strength between the two, thereby improving the overall structural stability of the composite lithium supplement material.

[0065] In one embodiment, the catalyst 30 is grown in situ on the one-dimensional carbon material 10. The one-dimensional carbon material 10 may be provided in advance, and then the one-dimensional carbon material 10 and the catalyst precursor are mixed, the catalyst precursor is attached to the one-dimensional carbon material 10, and finally the catalyst precursor is converted into the catalyst 30 by hydrothermal reduction treatment.

[0066] By in-situ growing the catalyst 30 on the surface of the one-dimensional carbon material 10, the catalyst 30 can fully contact the one-dimensional carbon material 10 and obtain a larger contact area, thereby exposing more active sites on the one-dimensional carbon material 10 and improving the overall conductivity of the one-dimensional carbon material 10 and the catalyst 30, thereby improving the catalytic activity of the catalyst 30; and the in-situ grown catalyst 30 has a smaller particle size, which is conducive to fully exerting the catalytic performance of the catalyst 30.

[0067] In one embodiment, the mass ratio of the sum of the one-dimensional carbon material 10 and the two-dimensional carbon material to the catalyst 30 is 10: (1 to 10). The sum of the one-dimensional carbon material 10 and the two-dimensional carbon material is the sum of the mass proportions of the two. Optionally, the mass ratio of the sum of the one-dimensional carbon material 10 and the two-dimensional carbon material to the catalyst 30 can be 10: 1, 10: 2, 10: 3, 10: 4, 10: 5, 10: 6, 10: 7, 10: 8, 10: 9, 10: 10.

[0068] Meeting the mass ratio of the carbon material and the catalyst 30 within the above range can ensure that the one-dimensional carbon material 10 and the two-dimensional carbon material cooperate with each other to increase the specific surface area and active sites. When the mass ratio of the carbon material is less than the above range, the one-dimensional carbon material 10 provides a small binding area, and some two-dimensional carbon materials or catalysts 30 are difficult to load on the one-dimensional carbon material 10, or the two-dimensional carbon material has limited contribution to the increased specific surface area and active sites of the catalytic material 200, and the conductivity and catalytic performance of the catalytic material 200 are limited. When the mass ratio of the catalyst 30 is less than the above range, the catalytic effect provided by the catalytic material 200 deteriorates, and the effect on reducing the voltage of the lithium-rich material 100 is limited.

[0069] In one embodiment, the specific surface area of ​​the one-dimensional carbon material 10 is 220 m 2 / g~280m 2 Optionally, the specific surface area of ​​the one-dimensional carbon material 10 can be 220 m 2 / g, 230m 2 / g, 240m 2 / g, 250m 2 / g, 260m 2 / g, 270m 2 / g, 280m 2 / g.

[0070] The present invention uses a one-dimensional carbon material 10 as a loading substrate for a two-dimensional carbon material and a catalyst 30, and utilizes non-metallic elements doped on the one-dimensional carbon material 10 to provide active sites, thereby improving the bonding strength between the two-dimensional carbon material and the one-dimensional carbon material 10, and increasing the loading amount of the catalyst 30. Therefore, satisfying that the specific surface area of ​​the one-dimensional carbon material 10 is within the above range can increase the loading amount of the two-dimensional carbon material and the catalyst 30, and increase the active sites of the two on the one-dimensional carbon material 10, thereby improving the lithium replenishment capacity and electrochemical performance of the composite lithium replenishment material. When the specific surface area of ​​the one-dimensional carbon material 10 is less than the above range, the loading amount of the two-dimensional carbon material and the catalyst 30 is small, not only the conductivity is limited, but also the effect of the catalyst 30 is weak.

[0071] In one embodiment, the particle size of the catalyst 30 is 2 nm to 50 nm. Optionally, the particle size of the catalyst 30 may be 2 nm, 4 nm, 6 nm, 10 nm, 20 nm, 30 nm, 40 nm, or 50 nm.

[0072] When the particle size of the catalyst 30 is within the above range, it can ensure that the catalyst 30 has a high catalytic performance, and can also reduce the difficulty of preparing the catalyst 30 and avoid agglomeration of the catalyst 30. When the particle size of the catalyst 30 is smaller than the above range, the difficulty of preparing the catalyst 30 increases, and the agglomeration of the catalyst 30 is serious, which affects the performance of its catalytic performance; when the particle size of the catalyst 30 is larger than the above range, the catalytic performance of the catalyst 30 decreases.

[0073] In one implementation, please refer to Figure 1 , the catalytic material 200 is embedded in the lithium-rich material 100, that is, the catalytic material 200 is located in the lithium-rich material 100 as a whole, thereby forming an integrated structure in which the lithium-rich material 100 covers the catalytic material 200. The catalytic material 200 is driven into the lithium-rich material 100 as a whole, so that the catalytic material 200 and the lithium-rich material 100 become a whole, so that the two have good contact, and the conductivity of the carbon material (including the one-dimensional carbon material 10 and the two-dimensional carbon material) and the catalytic performance of the catalyst 30 can be better exerted, so as to significantly reduce the delithiation potential of the lithium-rich material 100.

[0074] In one embodiment, the mass ratio of the lithium-rich material 100 to the catalytic material 200 is 100:(10-30). Optionally, the mass ratio of the lithium-rich material 100 to the catalytic material 200 may be 100:10, 100:15, 100:20, 100:25, or 100:30.

[0075] When the mass ratio of the lithium-rich material 100 and the catalytic material 200 is within the above range, the lithium replenishing capacity of the composite lithium replenishing material can be ensured, and the catalytic effect of the catalytic material 200 can be fully exerted, and the conductivity of the material can be ensured, and the delithiation potential of the lithium-rich material 100 can be reduced. When the mass proportion of the catalytic material 200 is less than the above range, the catalytic material 200 has limited improvement on the conductivity of the lithium-rich material 100, and the catalytic effect of the catalytic material 200 is poor. When the mass proportion of the above-mentioned catalytic material 200 is greater than the above range, the proportion of the lithium-rich material 100 will be further reduced, and the lithium-rich material 100 will find it difficult to exert more battery capacity, resulting in a decrease in the energy density of the battery.

[0076] In one embodiment, the particle size of the composite lithium supplement material is 1 μm to 5 μm. Optionally, the particle size of the composite lithium supplement material can be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, or 5 μm.

[0077] When the particle size of the composite lithium-supplementing material is within the above range, it can be ensured that the catalytic material 200 can be embedded in the lithium-rich material 100, and the lithium ions in the composite lithium-supplementing material can be fully released, and the composite lithium-supplementing material can be avoided from agglomerating. When the particle size of the composite lithium-supplementing material is smaller than the above range, it means that the particle size of the lithium-rich material 100 is small, the catalytic material 200 is difficult to embed into the lithium-rich material 100, and the composite lithium-supplementing material is easy to agglomerate; when the particle size of the composite lithium-supplementing material is larger than the above range, the difficulty of lithium ion deintercalation of the composite lithium-supplementing material increases, and the capacity of the material is difficult to fully release.

[0078] In this aspect, the composite lithium supplement material provided by the present invention includes a one-dimensional carbon material 10, a two-dimensional carbon material and a catalyst 30, wherein the two-dimensional carbon material is connected to it through the non-metallic elements on the one-dimensional carbon material, and the two-dimensional carbon material and the one-dimensional carbon material are connected through bond energy. Compared with the ordinary physical connection method, the connection strength between the two is high and the stability is strong; in addition, the non-metallic elements doped on the one-dimensional carbon material can improve the conductivity of the one-dimensional carbon material, and also provide more active sites for the adsorption of the two-dimensional carbon material and the loading of the catalyst 30. The adsorption of the two-dimensional carbon material on the one-dimensional carbon material can not only promote the formation of a more complete conductive path between the carbon materials, but also the two-dimensional carbon material can also provide abundant active sites for the loading of the catalyst 30.

[0079] Meanwhile, in this aspect, the composite lithium supplement material provided by the present invention includes a lithium-rich material 100 and a catalytic material 200 embedded in the lithium-rich material 100. After the catalytic material 200 and the lithium-rich material 100 are composited, the catalytic material 200 and the lithium-rich material 100 become a whole, have good contact, can better exert the conductivity of the carbon material and the catalytic performance of the catalyst 30, so as to significantly reduce the delithiation potential of the lithium-rich material 100.

[0080] In one embodiment, the present invention provides a method for preparing a composite lithium supplement material, please refer to Figure 3 , specifically used to prepare the composite lithium supplement material in the first aspect, comprising the following steps:

[0081] Step A10, mixing the one-dimensional carbon material and the catalyst precursor with the multi-dimensional carbon material respectively, and obtaining the catalytic material after heat treatment.

[0082] Step A20, mixing the catalytic material and the lithium-rich material together to obtain a composite lithium-supplementing material.

[0083] In one implementation, please refer to Figure 3 , before step A10, it also includes step A00: preparing a one-dimensional carbon material doped with a non-metallic element.

[0084] In step A00, a one-dimensional carbon material doped with non-metallic elements is prepared, which specifically includes: pre-treating the one-dimensional carbon material to produce active sites on the one-dimensional carbon material, mixing the one-dimensional carbon material with raw materials of non-metallic elements for reaction, and grafting the non-metallic elements onto the active sites of the one-dimensional carbon material to obtain the one-dimensional carbon material doped with non-metallic elements.

[0085] Optionally, in step A00, the pretreatment of the one-dimensional carbon material may be specifically performed by acidifying the one-dimensional carbon material with an acidic solution, wherein the acidic solution includes but is not limited to H2SO4 and / or HNO3, etc. It is understandable that the acidification treatment causes defects in the one-dimensional carbon material, thereby exposing more active sites.

[0086] Optionally, in step A00, the raw material of the non-metallic element may be an organic matter containing the non-metallic element, such as thiourea.

[0087] In one implementation, please refer to Figure 4 , in step A10, the following steps are also included:

[0088] Step A11, mixing the one-dimensional carbon material containing non-metallic elements with the multi-dimensional carbon material, and after heat treatment, the one-dimensional carbon material is connected to the multi-dimensional carbon material through the non-metallic elements.

[0089] Step A12, mixing the catalyst precursor with the one-dimensional carbon material and the multi-dimensional carbon material, and after heat treatment, converting the catalyst precursor into a catalyst to obtain a catalytic material.

[0090] In step A11, the one-dimensional carbon material containing non-metallic elements is mixed with the multidimensional carbon material and subjected to heat treatment, specifically including: mixing the one-dimensional carbon material containing non-metallic elements with the multidimensional carbon material, and using a pretreatment agent to perform a pyrolysis reaction on the one-dimensional carbon material containing non-metallic elements so that the non-metallic elements on the one-dimensional carbon material are exposed and connected to the multidimensional carbon material.

[0091] Optionally, in step A11, the pre-treatment agent may be benzene disulfide.

[0092] In step A12, the catalyst precursor is mixed with the one-dimensional carbon material and the multi-dimensional carbon material, and after heat treatment, the catalyst precursor is converted into a catalyst, which specifically includes: dispersing the obtained one-dimensional carbon material and multi-dimensional carbon material composites together with the catalyst precursor in a solvent, performing a thermal reaction in a reactor to obtain a mixture, and after washing and drying, placing the mixture under an inert atmosphere for calcination to obtain a catalytic material.

[0093] Optionally, in step A12, the precursor of the catalyst may be a metal salt, and the solvent may be a mixed solvent of water and ethanol. In addition, the mixture obtained by the thermal reaction in the reactor may include hydroxide and carbon material, and after high-temperature calcination, the hydroxide is dehydrated and converted into a catalyst of a metal oxide.

[0094] In step A20, the catalytic material and the lithium-rich material are mixed together, specifically including: placing the catalytic material and the lithium-rich material in a ball mill for ball milling, using the impact force of the ball milling beads on the materials to drive the catalytic material as a whole into the lithium-rich material, forming an integrated structure in which the lithium-rich material covers the catalytic material.

[0095] In the second aspect, the present application also provides another composite lithium supplement material, please refer to Figure 5 The composite lithium supplement material includes a lithium-rich material 100, a one-dimensional carbon material 10, a multi-dimensional carbon material 20 and a catalyst 30. In this aspect, the type, structure and function of the one-dimensional carbon material 10 and the catalyst 30 can refer to the description of the first aspect; the type of the lithium-rich material 100 can also refer to the description of the first aspect, which will not be repeated here.

[0096] In this aspect, the multidimensional carbon material 20 is preferably a three-dimensional carbon material. In a specific embodiment, the multidimensional carbon material 20 is preferably a three-dimensional porous carbon (HPC), and the three-dimensional porous carbon is a porous structure with holes, and the one-dimensional carbon material 10 extends into the holes. It should be explained that the appearance and shape of the three-dimensional porous carbon are not specifically limited, and can be spherical, ellipsoidal, polyhedral, irregular granular, etc. In addition, the volume of the three-dimensional porous carbon is much larger than that of the one-dimensional carbon material 10, so that the one-dimensional carbon material 10 can extend into its holes.

[0097] In one implementation, please refer to Figure 5 The multidimensional carbon material 20 is a hierarchical porous structure with macropores, and the one-dimensional carbon material 10 is interspersed in the macropores. In addition, mesopores or micropores may also be distributed in the three-dimensional porous carbon.

[0098] Specifically, at least two holes with different pore size ranges are provided on the three-dimensional porous carbon, wherein the macropores are used for the one-dimensional carbon material 10 to pass through, and the mesopores or small pores are mainly used to adjust the volume changes that may occur during the reaction of the catalytic material 200, so the macropores and mesopores or small pores on the three-dimensional porous carbon have different functions. The unique hierarchical porous structure of the three-dimensional porous carbon can accelerate the rapid transfer of reactants and the migration of electrons, and the three-dimensional porous carbon has a larger active surface area, which increases the space utilization of the material. In addition, the holes on the three-dimensional porous carbon are also conducive to the escape of gases (such as CO2) generated by the lithium-rich material 100 during the delithiation process, protecting the structural integrity of the composite lithium-supplementing material.

[0099] In the specific implementation, please refer to Figure 5 The three-dimensional porous carbon can be in the shape of a polyhedron, and a plurality of macropores are opened from the outer surface of the three-dimensional porous carbon. Some of the macropores extend from one side of the three-dimensional porous carbon to the inside to form channels and penetrate from the other side, that is, the three-dimensional porous carbon is formed with channels of macropores that penetrate the inside. The one-dimensional carbon material 10 penetrates from the macropore openings on one side of the three-dimensional porous carbon and passes out from the macropore openings on the other side of the three-dimensional porous carbon. Optionally, the length of the one-dimensional carbon material 10 is greater than the length of the internal channel of the three-dimensional porous carbon, so that part of the one-dimensional carbon material 10 will be located outside the three-dimensional porous carbon, forming "tentacles" on the three-dimensional porous carbon. The advantage of the one-dimensional carbon material 10 penetrating the interior of the three-dimensional porous carbon is that the one-dimensional carbon material 10 can form a conductive fast channel, thereby increasing the transfer rate of ions or electrons in the three-dimensional porous carbon; and the part of the one-dimensional carbon material 10 extending out of the three-dimensional porous carbon also increases the basic area of ​​the carbon material and the lithium-rich material 100, thereby enhancing the conductive fast channel effect of the one-dimensional carbon material 10 and improving the conductivity of the lithium-rich material 100.

[0100] In the specific implementation, please refer to Figure 6 On the same surface of the three-dimensional porous carbon, at least some of the macropores are interconnected, that is, on the same surface of the three-dimensional porous carbon, the one-dimensional carbon material 10 enters from one of the macropores and exits from another macropore. In this way, there are "tentacles" formed by the one-dimensional carbon material 10 on any surface of the three-dimensional porous carbon, which increases the basic area of ​​the carbon material and the lithium-rich material 100.

[0101] In the specific implementation, please refer to Figure 5 and Figure 6, macropores and mesopores (or small pores) are formed on the same surface of the three-dimensional porous carbon, and both macropores and mesopores (or small pores) are open holes, that is, both are connected to the external space; wherein, the macropores are for the one-dimensional carbon material 10 to pass through, and the mesopores or small pores are used to accommodate gas. Optionally, mesopores or small pores are formed inside the three-dimensional porous carbon, and the mesopores or small pores can be formed on the inner wall surface of the macropore channel, so that the mesopores or small pores can be used to accommodate the gas formed inside the three-dimensional porous carbon and provide space for the one-dimensional carbon material 10 to expand or contract. In addition, mesopores or small pores are formed inside the three-dimensional porous carbon, and the mesopores or small pores can be blind holes, that is, the mesopores or small pores are independent of the macropores and the external space (not connected to the external space), and the mesopores or small pores are used to adapt to the volume change of the three-dimensional porous carbon.

[0102] In one embodiment, the pore size of the macropores ranges from 50 nm to 200 nm. Optionally, the pore size of the macropores may be 50 nm, 70 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, or 200 nm.

[0103] The pore size of the macropore is within the above range to ensure that the one-dimensional carbon material 10 can extend into the macropore, and because the same carbon material is grown in the pores of the three-dimensional porous carbon, it is also convenient to limit the diameter of the one-dimensional carbon material 10, thereby improving the conductivity of the one-dimensional carbon material 10. When the pore size of the macropore is smaller than the above range, the diameter of the one-dimensional carbon material 10 is too thin, and the one-dimensional carbon material 10 is difficult to load the catalyst 30. When the pore size of the macropore is larger than the above range, the diameter of the one-dimensional carbon material 10 is too thick, which is not conducive to the one-dimensional carbon material 10 to conduct electrons, and the excessively large pore size also affects the structural stability of the three-dimensional porous carbon.

[0104] In one embodiment, the pore size of the mesopore or small pore ranges from 2 nm to 20 nm. Optionally, the pore size of the mesopore or small pore can be 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, or 20 nm.

[0105] The pore size of the mesopores or small pores is within the above range to ensure the structural stability of the three-dimensional porous carbon and to ensure that the three-dimensional porous carbon has a suitable volume change space. When the pore size of the mesopores or small pores is smaller than the above range, the volume change of the three-dimensional porous carbon is limited, which is not conducive to adjusting the volume change of the catalytic material 200. When the pore size of the mesopores or small pores is larger than the above range, the mesopores or small pores approach the macropores, and the effect of graded pores cannot be achieved, and the excessive pore size also affects the structural stability of the three-dimensional porous carbon.

[0106] In one embodiment, the porosity of the three-dimensional porous carbon is 60% to 85%. Optionally, the porosity of the three-dimensional porous carbon can be 60%, 65%, 70%, 75%, 80%, or 85%.

[0107] The porosity of the three-dimensional porous carbon is within the above range, so that the three-dimensional porous carbon has a larger specific surface area to combine with the one-dimensional carbon material 10, and the structural stability of the three-dimensional porous carbon is ensured. When the porosity of the three-dimensional porous carbon is less than the above range, the specific surface area of ​​the three-dimensional porous carbon is limited, which is not conducive to increasing the loading amount of the one-dimensional carbon material 10 and the catalyst 30, and the lithium-rich material 100 can also be stably combined with the three-dimensional porous carbon. When the porosity of the three-dimensional porous carbon is greater than the above range, the structural stability of the three-dimensional porous carbon deteriorates, and the overall strength of the catalytic material 200 deteriorates.

[0108] In one embodiment, the one-dimensional carbon material 10 and the multidimensional carbon material 20 (three-dimensional porous carbon) are connected by chemical bonds, and the chemical bonds include one or more of CC, CS, CN, CO, CP, C=C, C=O, and C=N. It should be explained that the one-dimensional carbon material 10 can be in-situ grown in the pores of the three-dimensional porous carbon, so the carbon elements in the one-dimensional carbon material 10 can form chemical bonds (such as CC) with the carbon elements in the multidimensional carbon material 20.

[0109] In one embodiment, the one-dimensional carbon material 10 and the three-dimensional porous carbon are both doped with non-metallic elements, and the non-metallic elements include at least one of O, N, S, and P. Therefore, chemical bonds can also be formed between the non-metallic elements and carbon elements on the one-dimensional carbon material 10 and the three-dimensional porous carbon.

[0110] The combination of the one-dimensional carbon material 10 and the three-dimensional porous carbon provided by the present invention needs to be distinguished from the mixing of porous carbon and carbon nanotubes in the prior art. In the prior art, the mixing of porous carbon and carbon nanotubes is mostly carried out by ball milling or mixed sintering, so that the surfaces of the two are connected to each other. In the present invention, the one-dimensional carbon material 10 extends into the three-dimensional porous carbon, which is difficult to achieve by simple ball milling or sintering; and the one-dimensional carbon material 10 extending into the hole is connected to the three-dimensional porous carbon (especially the inner wall of the hole) through the non-metallic elements doped thereon, and a chemical bond can be formed. In this way, the one-dimensional carbon material 10 is anchored in the three-dimensional porous carbon by the non-metallic elements, which can not only improve the connection strength between the two, improve the structural stability, but also improve the efficiency of conducting electrons between the two.

[0111] In one implementation, please refer to Figure 5 and Figure 6 The one-dimensional carbon material 10 is a hollow structure, and at least part of the catalyst 30 is contained in the one-dimensional carbon material 10. In this aspect, the interior of the one-dimensional carbon material 10 is hollow, and the catalyst 30 is contained in the interior of the one-dimensional carbon material 10. The one-dimensional carbon material 10 protects the catalyst 30, and sealing the catalyst 30 therein can reduce possible side reactions between the catalyst 30 and the electrolyte.

[0112] In one embodiment, the catalyst 30 includes a first catalyst and a second catalyst that are different, and the first catalyst and the second catalyst are interconnected to form a heterojunction.

[0113] In this aspect, the first catalyst comprises a metal oxide, the second catalyst comprises a metal element, and the transition metal element of the metal oxide and the metal element is the same. The chemical formula of the metal oxide comprises D1 n O m , wherein D1 is a transition metal element, D1 includes at least one of Co, Mo, W, V, Ti, Fe, Ni, Mn, Cr, Cu, and Zn, 1≤n≤3, and 1≤m≤3. In a specific embodiment, the first catalyst includes one or more of CoO, MnO, NiO, etc., and the second catalyst includes one or more of Co, Mn, Ni, etc. Therefore, in a specific embodiment, the catalyst 30 can be a Co / CoO heterojunction, a Ni / NiO heterojunction, or a Mn / MnO heterojunction; and through the protective effect of the one-dimensional carbon material 10, the catalyst 30 with catalytic activity (such as a Co / CoO heterojunction) is sealed to reduce the side reactions that may occur between the single substance in the heterojunction and the electrolyte.

[0114] It should be explained that the first catalyst and the second catalyst are connected, and a heterojunction is formed at the connection, the first catalyst and the second catalyst share the transition metal ions in the heterojunction, and the transition metal ions are connected to the oxygen ions in the first catalyst. Therefore, the transition metal ions in the heterojunction are used to form the crystal structure of the first catalyst and the second catalyst. It can be understood that in this aspect, the heterojunction is similar to a "double-sided adhesive" with a two-way connection function, and the heterojunction is connected to the first catalyst on one side and the second catalyst on the other side, so that the two are closely connected.

[0115] The heterojunction catalyst 30 can improve its own catalytic performance and conductivity, thereby improving the electron transfer efficiency and catalytic activity of the lithium-rich material 100; by catalyzing the lithium-rich material 100 through the heterojunction catalyst 30, on the one hand, the conductivity of the lithium-rich material 100 can be improved, and on the other hand, the decomposition voltage of the lithium-rich material 100 can be effectively reduced, so that it can be decomposed at a smaller voltage to release capacity, thereby achieving a high lithium replenishment capacity.

[0116] In one embodiment, the heterojunction catalyst 30 is in-situ grown on the one-dimensional carbon material 10. The first catalyst and the second catalyst are obtained by reacting the same precursor. Therefore, it can be understood that by controlling the conversion process of the precursor, the obtained product includes both the first catalyst and the second catalyst. Different from the single catalyst 30 in the prior art, the heterojunction catalyst 30 has a better catalytic effect, and the preparation method is simple and efficient.

[0117] In one embodiment, the mass ratio of the sum of the one-dimensional carbon material 10 and the three-dimensional porous carbon to the catalyst 30 is 10:(1.5-3.5). The sum of the one-dimensional carbon material 10 and the three-dimensional porous carbon is the sum of their mass proportions. Optionally, the mass ratio of the sum of the one-dimensional carbon material 10 and the three-dimensional porous carbon to the catalyst 30 can be 10:1.5, 10:2, 10:2.5, 10:3, 10:3.5.

[0118] When the mass ratio of the carbon material and the catalyst 30 is within the above range, it can ensure that the one-dimensional carbon material 10 and the three-dimensional porous carbon cooperate with each other to increase the specific surface area and active sites. When the mass ratio of the carbon material is less than the above range, the one-dimensional carbon material 10 and the three-dimensional porous carbon supporting the catalyst 30 account for too little, resulting in poor conductivity of the catalytic material 200. When the mass ratio of the catalyst 30 is less than the above range, the catalytic effect provided by the catalytic material 200 deteriorates, and the effect on reducing the voltage of the lithium-rich material 100 is limited.

[0119] In one embodiment, the specific surface area of ​​the three-dimensional porous carbon is 1000 m 2 / g~3000m 2 / g. Optionally, the specific surface area of ​​the three-dimensional porous carbon can be 1000m 2 / g、1500m 2 / g, 2000m 2 / g、2500m 2 / g、3000m 2 / g.

[0120] The present invention loads one-dimensional carbon material 10 and catalyst 30 on three-dimensional porous carbon, and utilizes the rich pore structure on the three-dimensional porous carbon to expose more active sites, so that the one-dimensional carbon material 10 is interspersed in the holes and combined with it through non-metallic elements, thereby improving the stability of the catalytic material 200. Therefore, if the specific surface area of ​​the three-dimensional porous carbon is within the above range, the loading amount of the one-dimensional carbon material 10 and the catalyst 30 can be increased, and the active sites of the two on the three-dimensional porous carbon can be increased, thereby improving the lithium replenishment capacity and electrochemical performance of the composite lithium replenishment material. When the specific surface area of ​​the three-dimensional porous carbon is less than the above range, the loading amount of the one-dimensional carbon material 10 and the catalyst 30 is small, not only the conductivity is limited, but also the effect of the catalyst 30 is weak.

[0121] In one embodiment, the particle size of the catalyst 30 is 2 nm to 20 nm. Optionally, the particle size of the catalyst 30 may be 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, or 20 nm.

[0122] When the particle size of the catalyst 30 is within the above range, it can be ensured that the catalyst 30 can be accommodated in the one-dimensional carbon material 10, and the catalyst 30 does not block the pores of the one-dimensional carbon material 10 to provide stable catalytic performance, and it can also reduce the difficulty of preparing the catalyst 30 and avoid agglomeration of the catalyst 30. When the particle size of the catalyst 30 is smaller than the above range, the difficulty of preparing the catalyst 30 increases, and the agglomeration of the catalyst 30 is serious, which affects the performance of its catalytic performance; when the particle size of the catalyst 30 is larger than the above range, the catalyst 30 is difficult to be accommodated in the pores of the one-dimensional carbon material 10, or the pores may be blocked.

[0123] In one implementation, please refer to Figure 7 , the catalytic material 200 is coated on the periphery of the lithium-rich material 100, that is, the outer surface of the lithium-rich material 100 is coated with a coating layer, and the coating layer includes a plurality of particles of the catalytic material 200. The catalytic material 200 provided in the present application can be used to reduce the particle size of the lithium-rich material 100. In a specific embodiment, the lithium-rich material 100 can be an organic lithium-rich material 100, and the organic lithium-rich material 100 is bonded to the catalytic material 200 by recrystallization. The coating layer formed by the catalytic material 200 confines the organic lithium-rich material 100, thereby achieving the effect of reducing the particle size.

[0124] In one embodiment, the mass ratio of the lithium-rich material 100 to the catalytic material 200 is 100:(5-35). Optionally, the mass ratio of the lithium-rich material 100 to the catalytic material 200 may be 100:5, 100:10, 100:15, 100:20, 100:25, 100:30, 100:35.

[0125] When the mass ratio of the lithium-rich material 100 and the catalytic material 200 is within the above range, the lithium replenishing capacity of the composite lithium replenishing material can be ensured, and the catalytic effect of the catalytic material 200 can be fully exerted, and the conductivity of the material can be ensured, and the delithiation potential of the lithium-rich material 100 can be reduced. When the mass proportion of the catalytic material 200 is less than the above range, the catalytic material 200 has limited improvement on the conductivity of the lithium-rich material 100, and the catalytic effect of the catalytic material 200 is poor. When the mass proportion of the above-mentioned catalytic material 200 is greater than the above range, the proportion of the lithium-rich material 100 will be further reduced, and the lithium-rich material 100 will find it difficult to exert more battery capacity, resulting in a decrease in the energy density of the battery.

[0126] In this aspect, the catalytic material 200 provided by the present invention includes a one-dimensional carbon material 10, a three-dimensional porous carbon and a catalyst 30, wherein the one-dimensional carbon material has a protective effect, seals the catalyst 30 with catalytic activity, and prevents the catalyst 30 from reacting with the electrolyte; and the non-metallic elements doped on the one-dimensional carbon material are used to anchor it in the pores of the three-dimensional porous carbon, thereby increasing the structural stability of the three-dimensional porous carbon and the one-dimensional carbon material; and, the dense one-dimensional material distribution and the hierarchical porous structure on the three-dimensional porous carbon can accelerate the rapid transfer of reactants and the migration of electrons, and has a larger active surface area, thereby increasing the spatial utilization of the material.

[0127] Meanwhile, in this aspect, the composite lithium supplement material provided by the present invention comprises a lithium-rich material 100 and a catalytic material 200 coating the lithium-rich material 100. After the catalytic material 200 and the lithium-rich material 100 are composited, the particle size of the lithium-rich material 100 can be reduced, and the contact between the lithium-rich material 100 and the catalytic material 200 can be strengthened, which is conducive to the release of lithium ions; and the porous structure inside the catalytic material 200 is conducive to the overflow of the gas generated during the lithium removal process of the lithium-rich material 100, protecting the integrity of the material structure.

[0128] In one embodiment, the present invention provides a method for preparing a composite lithium supplement material, please refer to Figure 8 , specifically used to prepare the catalytic material and the composite lithium supplement material provided in the second aspect, comprising the following steps:

[0129] Step B10, respectively mixing the precursor of the catalyst and the precursor of the one-dimensional carbon material with the multi-dimensional carbon material, and obtaining the catalytic material after heat treatment.

[0130] Step B20, mixing the catalytic material and the lithium-rich material together to obtain a composite lithium-supplementing material.

[0131] In one implementation, please refer to Figure 8 , before step B10, it also includes step B00: preparing a multidimensional carbon material, and the multidimensional carbon material is three-dimensional porous carbon.

[0132] In step B00, a multidimensional carbon material is prepared, specifically comprising: mixing a multidimensional carbon material precursor and a pore-forming agent and drying them, heat-treating the dried powder, and placing the heat-treated product in an acid solution for washing.

[0133] Optionally, in step B00, the multidimensional carbon material precursor includes glucose and dicyandiamide, and the pore-forming agent includes sodium chloride and ferric chloride hexahydrate. The multidimensional carbon material precursor and the pore-forming agent are mixed and dried, including: sodium chloride, ferric chloride hexahydrate, glucose and dicyandiamide are sequentially added into ultrapure water to dissolve and mix, and after mixing evenly, freeze-drying is performed to obtain a mixture powder.

[0134] Optionally, in step B00, the dried powder is heat treated in an inert atmosphere at a temperature of 500°C-1000°C.

[0135] Optionally, in step B00, the product after heat treatment is placed in a H2SO4 solution for cleaning, and after soaking, filtering, washing with pure water, and vacuum drying, a multidimensional carbon material is obtained, wherein the H2SO4 concentration used is 0.5mol / L-5mol / L, the soaking time is 2h-10h, and the washing and drying temperature after acidification treatment is 60℃-100℃.

[0136] In one implementation, please refer to Fig. 9 In step B10, the following steps are also included:

[0137] Step B11, mixing the catalyst precursor with the multidimensional carbon material, and after heat treatment, the catalyst precursor grows on the multidimensional carbon material.

[0138] Step B12, mixing a one-dimensional carbon material precursor containing non-metallic elements with a multi-dimensional carbon material grown with a catalyst precursor, after heat treatment, the one-dimensional carbon material precursor is converted into a one-dimensional carbon material, the catalyst precursor is converted into a catalyst, and the catalyst is contained inside the one-dimensional carbon material.

[0139] Optionally, in step B11, the catalyst precursor includes a transition metal salt, which may be sulfate, phosphate, nitrate, etc. The multi-dimensional carbon material is mixed with auxiliary additives, such as PVP (polyvinyl pyrrolidone) and 2-methylimidazole.

[0140] In step B11, the catalyst precursor is mixed with the multidimensional carbon material, which may specifically include: adding the multidimensional carbon material, PVP and a transition metal salt to a methanol solution containing a trace amount of ammonia water to obtain a solution A, and then adding a methanol solution B containing 2-methylimidazole to the solution A, and obtaining a multidimensional carbon material with the catalyst precursor grown after sufficient stirring and thermal reaction treatment.

[0141] Optionally, in step B11, the heat treatment temperature after the mixture of solution A and solution B is 80°C-150°C, and the reaction is a hydrothermal reaction with a reaction time of 3h-6h. The methanol solution containing a trace amount of ammonia water is weakly alkaline and has a pH range of 7-9.

[0142] It should be explained that before adding solution B to solution A, 2 / 3 of the volume of the filtrate in solution A can be replaced with fresh methanol. In this embodiment, it is ensured that there is sufficient electrostatic adsorption of the multidimensional carbon material before the solution is diluted, so that the catalyst precursor grows best on the surface of the multidimensional carbon material nanochamber in the diluted solvent thermal reaction, and the catalyst precursor does not grow excessively in the solution.

[0143] Optionally, in step B12, the one-dimensional carbon material precursor containing non-metallic elements includes dicyandiamide (DCDA).

[0144] In step B12, a one-dimensional carbon material precursor containing non-metallic elements is mixed with a multidimensional carbon material on which a catalyst precursor is grown, and subjected to heat treatment, specifically including: placing the obtained multidimensional carbon material and the one-dimensional carbon material precursor containing non-metallic elements together at a high temperature for calcining, the one-dimensional carbon material precursor grows into a one-dimensional carbon material in the pores of the one-dimensional carbon material, and the catalyst precursor is converted into a catalyst and accommodated in the one-dimensional carbon material.

[0145] Optionally, in step B12, the environment for calcination at high temperature is an inert atmosphere, and the calcination temperature is 500°C-800°C, wherein a 500°C insulation section for 8 hours may be provided, and the calcination heating rate is 2°C / min.

[0146] In step B20, the catalytic material and the lithium-rich material are mixed together, specifically including: dissolving the lithium-rich material in water to form a saturated solution A, dispersing the catalytic material in ethanol to form a dispersed solution B, and adding the dispersed solution B to the coating solution A, so that the lithium-rich material is recrystallized and precipitated, and the catalytic material is coated on the periphery of the lithium-rich material.

[0147] Optionally, in step B20, the drying time after recrystallization is 6h-12h, and the temperature for removing crystal water is 150°C-300°C.

[0148] In this aspect, the catalyst and the preparation method of the composite lithium-supplementing material provided by the present invention are used to prepare a catalytic material of three-dimensional porous carbon, a one-dimensional carbon material and a catalyst composite, and a composite lithium-supplementing material of a catalytic material coated with a lithium-rich material. The preparation method is to grow a catalyst precursor on a multidimensional carbon material in advance, and then, while the multidimensional carbon material grows a one-dimensional carbon material, the catalyst precursor is converted into a catalyst and contained in the one-dimensional carbon material, thereby using the one-dimensional carbon material to protect the catalyst.

[0149] In one embodiment, the present invention further provides a positive electrode material, the positive electrode material includes an active material and a composite lithium supplement material. The composite lithium supplement material is the composite lithium supplement material provided in the above embodiment. Optionally, the active material is a positive electrode active material, which can be a phosphate positive electrode active material and a ternary positive electrode active material. In a specific embodiment, it includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium vanadium phosphate fluoride, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.

[0150] In one embodiment, the content of the composite lithium-supplementing material in the positive electrode material can be controlled at 1% to 6% of the mass of the positive electrode active material. This ratio can just make up for the loss of active lithium in the battery during the first charging process. If the amount of composite lithium-supplementing material added to the positive electrode material is too low, the active lithium lost in the positive electrode active material cannot be fully replenished, which is not conducive to improving the energy density and capacity retention rate of the battery. If the amount of composite lithium-supplementing material added to the positive electrode active material is too high, the original reversible capacity will be occupied and the cost will be increased. In some specific embodiments, in the positive electrode material, the mass percentage of the composite lithium-supplementing material can be 1%, 2%, 4%, 6%, etc.

[0151] In one embodiment, the present invention further provides a positive electrode plate, the positive electrode plate includes a current collector and an active material layer disposed on the current collector, the active material layer includes the composite lithium supplement material of any one of the above embodiments. Or the active material layer includes the composite lithium supplement material obtained by the preparation method of the composite lithium supplement material in the above embodiments.

[0152] In one embodiment, the positive electrode sheet includes a positive current collector, and the positive current collector has a positive active layer, and the positive active layer includes components such as positive active materials, composite lithium supplement materials, conductive agents, and binders. The present invention does not specifically limit these materials, and suitable materials can be selected according to actual application requirements. The positive current collector includes but is not limited to any one of copper foil and aluminum foil. The conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes, and the content of the conductive agent in the positive active layer is 3wt% to 5wt%. The types of binders include polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives, and the content of the binder in the positive active layer is 2wt% to 4wt%.

[0153] In one embodiment, the present invention further provides a secondary battery, the secondary battery comprising a negative electrode, a positive electrode and an electrolyte, wherein the positive electrode comprises the above-mentioned positive electrode material; the electrolyte may be an electrolyte, in which case the secondary battery also includes a diaphragm disposed between the positive electrode plate and the negative electrode plate; or, the electrolyte may be a solid electrolyte, in which case the diaphragm is not provided in the secondary battery and is replaced by a solid electrolyte.

[0154] The technical solution of the present invention is described in detail below through specific embodiments.

[0155] Example 1

[0156] This embodiment provides a composite lithium supplement material, which includes a catalytic material (CoO@SN-CNTs@GNS) and a lithium-rich material (Li2C2O4). The catalytic material is embedded in the lithium-rich material.

[0157] The catalytic material includes a one-dimensional carbon material doped with S element (hereinafter referred to as SN-CNTs, where SN is sulfur doping and CNTs is carbon nanotubes), a two-dimensional carbon material (hereinafter referred to as GNS), and a catalyst (CoO). The two-dimensional carbon material is connected to the outer surface of the one-dimensional carbon material through the S element to form a CS bond, and the catalyst is attached to the one-dimensional carbon material and the two-dimensional carbon material.

[0158] The mass ratio of carbon material (including one-dimensional carbon material and two-dimensional carbon material) to catalyst is 10:5; the specific surface area of ​​one-dimensional carbon material is 260m 2 / g, the particle size of the catalyst is 26nm; the mass ratio of the lithium-rich material to the catalytic material is 100:20; and the particle size of the composite lithium-supplementing material is 3μm.

[0159] The preparation method of the composite lithium supplement material comprises the following steps:

[0160] 1) The multi-walled carbon nanotubes were acidified by reacting with a mixture of concentrated H2SO4 and HNO3 (mass ratio 1:1) at 80°C for 5 hours, and then the multi-walled carbon nanotubes and thiourea were dissolved in anhydrous ethanol at a mass ratio of 1:5, and transferred to a reactor for sufficient reaction at 120°C for 3 hours, and nitrogen and sulfur were grafted onto the active sites of the carbon nanotubes by the chemical reaction between the carbon nanotubes and thiourea to obtain SN-CNTs.

[0161] 2) Weighing benzene disulfide and carbon nanotubes in a mass ratio of 3:1 for pyrolysis reaction, attaching 50% of the mass of graphene nanosheets on the carbon nanotube skeleton. Linking the carbon nanotubes and graphene through CS bonds, obtaining multifunctional carbon nanotubes SN-CNTs / GNS with more graphene sheets attached.

[0162] 3) The obtained multifunctional carbon nanotubes SN-CNTs / GNS and cobalt acetate tetrahydrate were dispersed in a mixed solution of water and ethanol in a volume ratio of 2:1, and a solvent thermal reaction was carried out in a reactor at 150°C for 6 hours. The obtained product was washed and dried to obtain Co(OH)2@SN-CNTs / GNS. Then, the product was subjected to high temperature heat treatment and decomposition at 400°C for 5 hours in an inert atmosphere to obtain CoO@SN-CNTs / GNS.

[0163] 4) The prepared CoO@SN-CNTs / GNS and Li2C2O4 were ball-milled at 500 r / min for 30 h. The impact force of the ball milling beads on the material was used to integrally beat the CoO@SN-CNTs / GNS into the interior of Li2C2O4, forming an integrated structure in which Li2C2O4 wrapped around CoO@SN-CNTs / GNS.

[0164] Example 2

[0165] This embodiment provides a composite lithium supplement material. The difference between this embodiment 2 and embodiment 1 is that the mass ratio of the carbon material to the catalyst is 10:1.

[0166] Example 3

[0167] This embodiment provides a composite lithium supplement material. The difference between this embodiment 3 and embodiment 1 is that the mass ratio of the carbon material to the catalyst is 10:10.

[0168] Example 4

[0169] This embodiment provides a composite lithium supplement material. The difference between this embodiment 4 and embodiment 1 is that the specific surface area of ​​the one-dimensional carbon material is 220m 2 / g.

[0170] Example 5

[0171] This embodiment provides a composite lithium supplement material. The difference between this embodiment 5 and embodiment 1 is that the specific surface area of ​​the one-dimensional carbon material is 280m 2 / g.

[0172] Example 6

[0173] This embodiment provides a composite lithium supplement material. The difference between this embodiment 6 and embodiment 1 is that the particle size of the catalyst is 2 nm.

[0174] Example 7

[0175] This embodiment provides a composite lithium supplement material. The difference between this embodiment 7 and embodiment 1 is that the particle size of the catalyst is 50 nm.

[0176] Example 8

[0177] This embodiment provides a composite lithium supplement material. The difference between this embodiment 8 and embodiment 1 is that the mass ratio of the lithium-rich material to the catalytic material is 100:10.

[0178] Example 9

[0179] This embodiment provides a composite lithium supplement material. The difference between this embodiment 9 and embodiment 1 is that the mass ratio of the lithium-rich material to the catalytic material is 100:30.

[0180] Example 10

[0181] This embodiment provides a composite lithium supplement material. The difference between this embodiment 10 and embodiment 1 is that the particle size of the composite lithium supplement material is 1 μm.

[0182] Embodiment 11

[0183] This embodiment provides a composite lithium supplement material. The difference between this embodiment 11 and embodiment 1 is that the particle size of the composite lithium supplement material is 5 μm.

[0184] Example 12

[0185] This embodiment provides a composite lithium supplement material. The difference between this embodiment 12 and embodiment 1 is that the lithium-rich material is lithium carbonate (Li2CO3).

[0186] Example 13

[0187] This embodiment provides a composite lithium supplement material. The difference between this embodiment 13 and embodiment 1 is that the catalyst is MnO2.

[0188] Embodiment 14

[0189] This embodiment provides a composite lithium supplement material, which includes a catalytic material (Co / CoO@NCNTs@3-HPC) and a lithium-rich material (Li2C2O4). The catalytic material is coated on the periphery of the lithium-rich material.

[0190] The catalytic material includes one-dimensional carbon material doped with N element (hereinafter referred to as NCNTs, where N is nitrogen doping and CNTs is carbon nanotubes), three-dimensional porous carbon (hereinafter referred to as 3-HPC), and catalyst (Co / CoO). Among them, the one-dimensional carbon material extends into the pores of the three-dimensional porous carbon and is anchored in the pores by the N element, and the catalyst is contained inside the one-dimensional carbon material.

[0191] The macropore size of the three-dimensional porous carbon is 100nm, the micropore size is 10nm; the porosity of the three-dimensional porous carbon is 75%; the mass ratio of carbon material (including one-dimensional carbon material and three-dimensional porous carbon) to catalyst is 10:2.5; the specific surface area of ​​the one-dimensional carbon material is 300m 2 / g, the particle size of the catalyst is 10nm; the mass ratio of the lithium-rich material to the catalytic material is 100:15.

[0192] The preparation method of the composite lithium supplement material comprises the following steps:

[0193] 1) 16g of NaCl, 40mg of ferric chloride hexahydrate, 2g of glucose, and 2g of dicyandiamide were added to 44mL of ultrapure water in sequence and dissolved. The obtained uniform solution was quickly freeze-dried into a precursor powder. The powder was further pyrolyzed in an argon atmosphere, and the products were soaked in 0.5M H2SO4 for 6 hours, filtered, washed with pure water, and vacuum dried to obtain 3-HPC. Among them, the heat treatment of the precursor powder was carried out at a rate of 5°C / min, and maintained at 550°C for 1 hour, and then maintained at 900°C for 2 hours.

[0194] 2) A 300 mL methanol solution (solution A) containing 0.5 g of 3-HPC, 0.5 mg of PVP (Wm = 40000 g / mol), 18.8 mmol of Co(NO3)2·6H2O and a trace of ammonia was stirred for 10 minutes, and then solution A was quickly poured into a 300 mL methanol solution B containing 0.15 mol of 2-methylimidazole. The above mixture was magnetically stirred for another 10 minutes and subjected to a solvothermal reaction at 120°C for 4 hours. Finally, the precipitate was filtered, washed, dried and collected.

[0195] 3) The precursor and dicyandiamide obtained in step 2) were respectively placed in the same porcelain boat and heated to 900° C. under Ar carrier gas. In order to obtain consistent and sufficient CNTs growth conditions, the heating rate was maintained at 2° C. / min and the temperature was maintained at 510° C. for 8 h.

[0196] 4) Lithium oxalate was dissolved in water to form a saturated lithium oxalate solution A, and Co / CoO@NCNTs / @3-HPC was ultrasonically dispersed in an ethanol solution to form a dispersed solution B. The dispersed solution B was added dropwise to the solution A to wrap the catalytic material on the surface of the lithium oxalate.

[0197] Embodiment 15

[0198] This embodiment provides a composite lithium supplement material. The difference between this embodiment 15 and embodiment 14 is that: the macropore diameter of the three-dimensional porous carbon is 200nm, the micropore diameter is 10nm; and the porosity of the three-dimensional porous carbon is 85%.

[0199] Example 16

[0200] This embodiment provides a composite lithium supplement material. The difference between this embodiment 16 and embodiment 14 is that: the macropore diameter of the three-dimensional porous carbon is 50nm, the micropore diameter is 10nm; and the porosity of the three-dimensional porous carbon is 60%.

[0201] Embodiment 17

[0202] This embodiment provides a composite lithium supplement material. The difference between this embodiment 17 and embodiment 14 is that: the macropore diameter of the three-dimensional porous carbon is 100nm, the micropore diameter is 2nm; and the porosity of the three-dimensional porous carbon is 55%.

[0203] Embodiment 18

[0204] This embodiment provides a composite lithium supplement material. The difference between this embodiment 18 and embodiment 14 is that: the macropore diameter of the three-dimensional porous carbon is 100 nm, the micropore diameter is 20 nm; and the porosity of the three-dimensional porous carbon is 80%.

[0205] Embodiment 19

[0206] This embodiment provides a composite lithium supplement material. The difference between this embodiment 19 and embodiment 14 is that the mass ratio of the carbon material to the catalyst is 10:1.5.

[0207] Embodiment 20

[0208] This embodiment provides a composite lithium supplement material. The difference between this embodiment 20 and embodiment 14 is that the mass ratio of the carbon material to the catalyst is 10:3.5.

[0209] Embodiment 21

[0210] This embodiment provides a composite lithium supplement material. The difference between this embodiment 21 and embodiment 14 is that the particle size of the catalyst is 2 nm.

[0211] Embodiment 22

[0212] This embodiment provides a composite lithium supplement material. The difference between this embodiment 22 and embodiment 14 is that the particle size of the catalyst is 20 nm.

[0213] Embodiment 23

[0214] This embodiment provides a composite lithium supplement material. The difference between this embodiment 23 and embodiment 14 is that the mass ratio of the lithium-rich material to the catalytic material is 100:5.

[0215] Embodiment 24

[0216] This embodiment provides a composite lithium supplement material. The difference between this embodiment 24 and embodiment 14 is that the mass ratio of the lithium-rich material to the catalytic material is 100:35.

[0217] Embodiment 25

[0218] This embodiment provides a composite lithium supplement material. The difference between this embodiment 25 and embodiment 14 is that the lithium-rich material is lithium carbonate (Li2CO3).

[0219] Embodiment 26

[0220] This embodiment provides a composite lithium supplement material. The difference between this embodiment 26 and embodiment 14 is that the catalyst is Ni / NiO.

[0221] Comparative Example 1

[0222] This comparative example provides a lithium-rich material (Li2C2O4).

[0223] Comparative Example 2

[0224] This comparative example provides a composite lithium supplement material, which includes a simple mixture of a lithium-rich material (Li2C2O4), a one-dimensional carbon material (SN-CNTs), a two-dimensional carbon material (GNS), and a catalyst (CoO).

[0225] Comparative Example 3

[0226] This comparative example provides a composite lithium supplement material, which includes a simple mixture of lithium-rich material (Li2C2O4), one-dimensional carbon material (NCNTs), three-dimensional porous carbon (3-HPC), and catalyst (Co / CoO).

[0227] The parameters of the composite lithium supplement materials provided by Examples 1 to 13 and Comparative Examples 1 to 2 are shown in Table 1:

[0228] Table 1 Parameters of the composite lithium supplement materials provided in Examples 1 to 13 and Comparative Examples 1 to 2

[0229]

[0230] The parameters of the composite lithium supplement materials provided by Examples 14 to 26 and Comparative Example 3 are shown in Table 2:

[0231] Table 2 Parameters of the composite lithium supplement materials provided in Examples 14 to 26 and Comparative Example 3

[0232]

[0233]

[0234] The composite lithium supplement materials provided in the above-mentioned Examples 1 to 26 and the composite lithium supplement materials provided in Comparative Examples 1 to 3 are respectively assembled into positive electrode sheets and lithium-ion batteries according to the following methods:

[0235] Positive electrode sheet: The composite lithium supplement material, SP and PVDF are mixed in a mass ratio of 90:4:6 to prepare a positive electrode slurry, the positive electrode slurry is coated on the surface of aluminum foil, vacuum dried at 110°C overnight, and rolled to obtain a positive electrode sheet;

[0236] Negative electrode: lithium sheet;

[0237] Electrolyte: Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and LiPF6 was added to form an electrolyte, and the concentration of LiPF6 was 1 mol / L;

[0238] Diaphragm: Polypropylene microporous separator;

[0239] Lithium-ion battery assembly: Assemble button-type lithium-ion full batteries in an inert atmosphere glove box in the order of negative electrode sheet - separator - electrolyte - positive electrode sheet.

[0240] The electrochemical performance of each lithium-ion battery assembled in the above lithium-ion battery embodiment was tested under the following test conditions:

[0241] The battery was charged at a rate of 0.1C with a cut-off voltage of 4.7V; constant voltage charging was performed at a cut-off voltage of 4.7V; after the charging process was completed, the battery was allowed to stand for 10 minutes and then discharged at a rate of 0.1C with a cut-off voltage of 2.5V; the charging platform was observed during the charging process to obtain the delithiation potential of the composite lithium supplement material.

[0242] The test results of the above composite lithium supplement material and lithium battery are shown in Table 3 and Table 4 below:

[0243] Table 3. Test results of Example 1-Example 13, Comparative Example 1-Comparative Example 2

[0244]

[0245]

[0246] Table 4 Test results of Example 14-Example 26 and Comparative Example 3

[0247]

[0248] It can be seen from the performance test results of Examples 1 to 13 in Table 3 that embedding a catalytic material composed of a carbon material and a catalyst in a lithium-rich material with a high delithiation potential can not only reduce its delithiation potential, but also improve the initial charge capacity and the specific charge capacity below 4.3 V. When the catalyst loaded on the carbon material (one-dimensional carbon material and two-dimensional carbon material) is used as the catalytic material as a whole, the catalytic material is suitable for the composite lithium supplement additive system under different mass ratios of carbon material to catalyst, specific surface area of ​​one-dimensional carbon material, catalyst particle size, mass ratio of lithium-rich material to catalytic material, particle size of composite lithium supplement material, type of catalyst and type of lithium-rich material.

[0249] It can be seen from the performance test results of Example 1 and Comparative Example 1 in Table 3 that when no catalytic material is added and only the lithium-rich material is present, the lithium-rich material in Comparative Example 1 has a higher delithiation potential, greater than 4.7V, and a low first charge capacity, and a lower charge capacity below 4.3V.

[0250] From the performance test results of Example 1 and Comparative Example 2 in Table 3, it can be seen that when the lithium-rich material (Li2C2O4), one-dimensional carbon material (SN-CNTs), two-dimensional carbon material (GNS), and catalyst (CoO) are simply mixed, the delithiation potential of the composite lithium supplement material in Comparative Example 2 is reduced, and the first charge specific capacity is increased. However, compared with the composite lithium supplement material provided in the embodiment, it is still insufficient, so it is explained that simply mixing the four provides far less performance effect on the material than the solution provided in this application.

[0251] From the performance test results of Example 1 to Example 3 in Table 3, it can be seen that different mass ratios of carbon material and catalyst will affect the catalytic performance of the catalytic material, but both can catalyze the lithium-rich material. When the proportion of catalyst is too low, it will affect the overall catalytic performance of the catalytic material, resulting in an increase in the delithiation potential and a decrease in the first-cycle charging capacity. When the proportion of catalyst is too high, the proportion of carbon will decrease under the same mass, causing the overall conductivity of the catalytic material to be slightly worse, and will also affect the overall catalytic performance of the catalytic material. Therefore, when the mass ratio of carbon material and catalyst is moderate, the catalytic performance of the catalyst and the conductivity of the conductive material can be taken into account. At this time, the catalytic material has better catalytic performance.

[0252] From the performance test results of Example 1, Example 4 and Example 5 in Table 3, it can be seen that the different specific surface areas of one-dimensional carbon materials will affect the catalytic performance of the catalyst material, but they can all play a catalytic role on the lithium-rich material. When the specific surface area of ​​the one-dimensional carbon material is too small, the corresponding diameter size is larger. The same material size is larger and often corresponds to its poor conductivity, which will affect the overall conductivity of the catalyst material, thereby affecting the catalytic performance. When the specific surface area of ​​the one-dimensional carbon material is too large, the corresponding diameter is smaller, which is not conducive to the attachment of the two-dimensional carbon material and the loading of the catalyst, so it affects the contact between the three, so it affects the catalytic performance. Therefore, when the specific surface area of ​​the one-dimensional carbon material is moderate, its conductivity and contact with the catalyst and the two-dimensional carbon material can be taken into account. At this time, the catalyst material has good catalytic performance.

[0253] From the performance test results of Example 1, Example 6 and Example 7 in Table 3, it can be seen that different particle sizes of the catalyst will affect the catalytic performance of the catalytic material, but can all catalyze the lithium-rich material. When the catalyst particle size is too small, agglomeration is likely to occur, and the agglomeration between the catalyst particles is not conducive to uniform contact with the carbon material, which will affect the catalytic performance. When the catalyst particle size is too large, the corresponding specific surface area is small, and the contact sites between the carbon material and the lithium-rich material become less, which is not conducive to exerting good catalytic performance. Therefore, when the catalyst particle size is moderate, the contact between the carbon material can be guaranteed to obtain better catalytic performance.

[0254] It can be seen from the performance test results of Example 1, Example 8 and Example 9 in Table 3 that different mass ratios of lithium-rich materials and catalytic materials will affect the capacity of lithium-rich materials. When the proportion of catalytic materials is too small, the proportion of lithium-rich materials is too large, and there is not enough catalytic material to catalyze the lithium-rich materials. Only a part of the lithium-rich materials can be catalyzed, so the capacity of the lithium-rich materials will be affected at this time. When the proportion of catalytic materials is too large, although the catalytic materials can play a better catalytic role and can reduce the lithium delithiation potential of lithium-rich materials, due to the high proportion of catalytic materials, the proportion of catalysts and carbon materials is relatively high, and these two are easy to react with electrolytes, affecting the capacity of lithium-rich materials. Therefore, when the amount of catalytic material added is moderate, better catalytic performance can be obtained.

[0255] From the performance test results of Example 1, Example 10 and Example 11 in Table 3, it can be seen that different particle sizes of the composite lithium supplement material will affect the capacity of the lithium-rich material. When the particle size of the composite lithium supplement material is too small, it is easy to agglomerate, which is not conducive to contact with the electrolyte, and cannot timely transfer Li + When the particle size of the composite lithium supplement is too large, there is a limitation in the way of ball milling the catalytic material into the interior of the lithium-rich material, and it cannot be ensured that the catalytic material can enter the center of the lithium-rich material. Therefore, when the composite lithium supplement material is large, the proportion of catalytic material per unit volume is low, resulting in poor catalytic performance, a higher corresponding delithiation potential, and a lower capacity.

[0256] It can be seen from the performance test results of Example 1, Example 12 and Example 13 in Table 3 that the solution provided by the present invention is also applicable to other lithium-rich materials or catalysts, indicating that the solution provided by the present invention is universal and can be applied to large-scale commercial applications.

[0257] It can be seen from the performance test results of Examples 14 to 26 in Table 4 that coating the outer surface of a lithium-rich material with a high delithiation potential with a catalytic material composed of a carbon material and a catalyst can significantly reduce the delithiation potential and powder resistivity of the lithium-rich material, and can effectively improve the initial charging capacity.

[0258] From the performance test results of Example 14 and Comparative Example 1 in Table 3 and Table 4, it can be seen that the delithiation potential and powder resistivity of the material in Example 14 are significantly lower than those in Comparative Example 1, and the delithiation capacity at low voltage is significantly improved. The reason is that the original lithium oxalate has a large particle size and poor conductivity; by coating the catalytic material on the lithium-rich material, not only can the delithiation potential be effectively reduced, but also the conductivity of the material can be improved.

[0259] It can be seen from the performance test results of Example 14 and Comparative Example 3 in Table 4 that when the lithium-rich material (Li2C2O4), one-dimensional carbon material (NCNTs), three-dimensional porous carbon (3-HPC) and catalyst (Co / CoO) are simply mixed, the catalyst will have side reactions with the electrolyte due to the lack of protection of the catalyst, and simple mixing may cause uneven contact of the materials, resulting in poor catalytic effect.

[0260] From the performance test results of Examples 14-18 in Table 4, it can be seen that the pore size distribution and porosity on the three-dimensional porous carbon will affect the catalytic performance of the catalytic material, but they can all play a catalytic role on lithium-rich materials. Among them, when the aperture of the macropores on the three-dimensional porous carbon is too large, the carbon tubes cannot contact the tube wall during the growth process, and it is difficult to play a supporting role. In addition, the aperture is relatively large, which may cause the catalyst to agglomerate during the growth process, affecting the catalytic effect of the material. When the aperture of the macropores on the three-dimensional porous carbon is too small, it is not conducive to the growth of carbon tubes in the nano chamber, and may reduce the catalytic active sites of the material. At the same time, when the aperture of the small pores on the three-dimensional porous carbon is too small, the three-dimensional porous carbon cannot restrict the gas, and it is difficult to adapt to the changes in the volume contraction and expansion of the carbon material. When the aperture of the small pores on the three-dimensional porous carbon is too large, the porosity of the material is too large, the material stability is poor, and it is easy to collapse during the catalytic process.

[0261] From the performance test results of Example 14, Example 19 and Example 20 in Table 4, it can be seen that the different mass ratios of carbon material and catalyst will affect the catalytic performance of the catalytic material, but can all catalyze the lithium-rich material. When the proportion of the growing catalyst is too low, it is not possible to fully catalyze the decomposition of lithium oxalate at low voltage. When the proportion of the growing catalyst is too high, the catalyst easily agglomerates and blocks the channels of the one-dimensional carbon material, thereby affecting the catalytic effect.

[0262] From the performance test results of Example 14, Example 21 and Example 22 in Table 4, it can be seen that different particle sizes of the catalyst will affect the catalytic performance of the catalytic material, but all can catalyze the lithium-rich material. When the catalyst particle size is too small, agglomeration is likely to occur during growth and subsequent treatment, and it is easy to block the pores of the carbon material, which may affect the catalytic effect of the catalytic material. When the catalyst particle size is too large, it affects the activity of the catalyst itself and the conductivity of the catalytic material, thereby causing the catalytic performance of the catalytic material to decrease.

[0263] From the performance test results of Example 14, Example 23 and Example 24 in Table 4, it can be seen that the different mass ratios of lithium-rich materials and catalytic materials will affect the capacity of lithium-rich materials. When the proportion of catalytic material is too small, the contact between the catalytic material and the lithium-rich material is not sufficient, resulting in poor performance of the composite lithium-supplementing material. When the proportion of catalytic material is too large, the delithiation potential of the lithium-rich material can be effectively reduced, but due to the excessive carbon content, other side reactions may occur in the composite lithium-supplementing material, resulting in a rapid increase in the delithiation potential in the subsequent process, and a low delithiation capacity in the low voltage state.

[0264] It can be seen from the performance test results of Example 14, Example 25 and Example 26 in Table 4 that the solution provided by the present invention is also applicable to other lithium-rich materials or catalysts, indicating that the solution provided by the present invention is universal and can be applied to large-scale commercial applications.

[0265] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship of the accompanying drawings, which are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0266] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiment and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. A composite lithium supplement material, characterized in that: The invention comprises a lithium-rich material, a one-dimensional carbon material, a multi-dimensional carbon material and a catalyst, wherein the chemical formula of the lithium-rich material comprises Li x1 C y1 O z1 , where 0<x1≤2,y1> 0, z1>0; the one-dimensional carbon material is connected to the multi-dimensional carbon material, at least a portion of the catalyst is loaded on the one-dimensional carbon material, and the lithium-rich material is combined with the one-dimensional carbon material and / or the multi-dimensional carbon material.

2. The composite lithium supplement material according to claim 1, characterized in that: The multidimensional carbon material is arranged and connected to the outside of the one-dimensional carbon material; or, the multidimensional carbon material is a porous structure with holes, and the one-dimensional carbon material extends into the holes of the multidimensional carbon material.

3. The composite lithium supplement material according to claim 1, characterized in that: The multidimensional carbon material has macropores, and the one-dimensional carbon material is interspersed in the macropores; and / or, mesopores or micropores are also distributed in the multidimensional carbon material; and / or, the porosity of the multidimensional carbon material is 60% to 85%.

4. The composite lithium supplement material according to claim 1, characterized in that: The one-dimensional carbon material is doped with non-metallic elements, and the non-metallic elements include at least one of O, N, S, and P; and / or the one-dimensional carbon material and the multidimensional carbon material are connected by chemical bonds, and the chemical bonds include one or more of CC, CS, CN, CO, CP, C=C, C=O, and C=N.

5. The composite lithium supplement material according to claim 1, characterized in that: The one-dimensional carbon material is a hollow structure, and at least a portion of the catalyst is contained in the one-dimensional carbon material; and / or, the catalyst includes a first catalyst and a second catalyst, and the first catalyst and the second catalyst are interconnected to form a heterojunction.

6. The composite lithium supplement material according to claim 1, characterized in that: The mass ratio of the sum of the one-dimensional carbon material and the multi-dimensional carbon material to the catalyst is 10:(1-10); and / or The specific surface area of ​​the one-dimensional carbon material is 100 m 2 / g~400m 2 / g; and / or The specific surface area of ​​the multidimensional carbon material is 1000 m 2 / g~3000m 2 / g; and / or The particle size of the catalyst is 2nm to 50nm.

7. The composite lithium supplement material according to claim 1, characterized in that: The one-dimensional carbon material, the multi-dimensional carbon material and the catalyst together constitute a catalytic material, the catalytic material is embedded in the lithium-rich material, or the catalytic material is coated on the periphery of the lithium-rich material; and / or The mass ratio of the lithium-rich material to the catalytic material is 100:(5-35).

8. A method for preparing a composite lithium supplement material, characterized in that: include: The one-dimensional carbon material and the precursor of the catalyst are mixed with the multi-dimensional carbon material respectively, or the precursor of the catalyst and the precursor of the one-dimensional carbon material are mixed with the multi-dimensional carbon material respectively, and the catalytic material is obtained after heat treatment; The catalytic material and the lithium-rich material are mixed together to obtain a composite lithium-supplementing material.

9. A positive electrode material, characterized in that: The positive electrode material includes an active material and a composite lithium-replenishing material, and the composite lithium-replenishing material includes the composite lithium-replenishing material according to any one of claims 1 to 7, or includes the composite lithium-replenishing material obtained by the preparation method of the composite lithium-replenishing material according to claim 8.

10. A secondary battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the positive electrode material as claimed in claim 9.